Evolução geológica e contextualização tectônica do bloco Cristalândia do Piauí, Faixa Rio Preto, Piauí/Bahia - Renato de Assis Barros (2019)
The Cristalândia do Piauí Block, located in the northwestern margin of the São Francisco Craton (SFC), represents the basement of the Rio Preto Fold Belt. It is composed of Archaean tonalitic to granodioritc orthogneisses crystalized in ca. 3.2 Ga that was reworked at 2.81 and 2.68 Ga with juvenile to moderately juvenile εHf values between -1.51 to -8.07, high-K syenogranitic gneisses dated at 2.65 Ga with crustal εHf values between -10.37 to -19.54, both with TDMc model ages varing from 3.57 to 4.33 Ga, indicating cryptic Paleo to Eo-archean and even Hadean sources, metamafic-ultramafic rocks, iron formations, metacherts and graphite schists. The whole set is intruded by Paleoprotezoic metagranitoids with compositions varying from granodioritic, with sanukitoid-type signatures, crystallized in ca. 2.2 Ga, with juvenile and crustal sources, to monzogranitic and alkali-fedspatic granitic with crustal signatures. They are related with the Rhyacian-Orosirian Orogeny, responsible for the complex deformation patterns printed in the Archean basement. Orosirian metassedimentary rocks are represented by garnet-biotite paragneiss, with maximum depositional age at ca 1.95 Ga. Garnet-amphibolite dykes intrusive in the complex show ages of ca 2.07 Ga and isotopic features of mantle-derived magmas. Considering the presented data, the Cristalândia do Piauí Block represents a metacratonic domain corresponding to part of the Guanambi-Correntina Block, involved in crustal accretion and reworking from the Archean to the Paleoproterozoic. This crustal segment was further rifted apart from the Guanambi-Correntina block during the Tonian taphrogenesis, with the development of a Neoproterozoic rift basin which would be filled by sedimentary rocks of the Canabravinha Formation. During the Ediacaran-Cambrian, far-field induced stresses related to the Brasiliano Orogeny would cause the inversion, deformation and metamorphism of the rift basin along with the basement represented by the Cristalândia do Piauí block, with corresponding Brasiliano metamorphism imprinted throughout the area. Many of the elements of the evolutionary stages present in the São Francisco-Congo Paleocontinent (SFCP) can be recognized, suggesting evolution of this crustal segment amounts to the Eo-Archean era and disclosing the existence of cryptic Paleo-archean or even Hadean nuclei, reworked in at least three metamorphic events during the Rhyacian-Orosirian orogeny.